Knowledge, attitude, and practice of COVID-19 among the exposed frontline police workers in Eastern Uttar Pradesh Region: An exploratory study - Jaya Singh; Shruti Singh; Trupti Jain; Dinesh Raja; Akhilesh Chandra; Mahesh Khairnar; P G Naveen; Rahul Agrawal (Wolters Kluwer Medknow Publications, 2024)
Background: The world has been hit by an unknown obstacle in the form of the COVID-19 pandemic. India also faced a never seen before situation in trying to contain the spread of COVID-19 by enforcing one of the most stringent lockdowns in the world. The billion-plus population of the country throws a severe challenge at the operational level in enforcing the measures. The frontline workers in these trying times such as the Police, Central Industrial Security Force, health-care workers, volunteers, and essential service workers have done a praiseworthy job under exceptionally hard conditions. Aim: The study aimed to investigate the awareness of COVID-19 among the frontline police workers who were posted during lockdown in our state. Materials and Methods: A questionnaire comprising 25 questions was randomly distributed among the police personnel who were on COVID-19 duty. The knowledge they had was assembled, assessed, and scrutinized. Results: A total of 150 police officers took part in the study. Mean age of 39.91 ± 9.96 years was seen. The majority of them had enough knowledge about the ongoing pandemic and they were seen to be taking good precautions to fight the virus. Conclusion: The joint effort of public and the frontline workers was the mainstream reason to bring our country back on track. Police had put their best efforts into controlling the spread of this contagion by maintaining a strict lockdown. They did immensely well and we as citizens should be grateful to them for protecting us from this pandemic.